ANALYSIS OF DEFECTIVE QUALITY CONTROL OF POWDERED DRINKS USING THE SIX SIGMA METHOD ON MULTILANE MACHINES - Probo Kusumo; Aries Susanti; Sri Hartini (Center for Study and Journal Management FTI UMI, 2022)
This observation aims to identify the types of defects that occur in the powder packaging process at PT. XYZ as an effort to improve product quality. By doing this observation, the benefits obtained include being able to find out what problems cause disability and be able to overcome these defects from the suggestions given by observers. The multi lane machine is a packaging machine that is the object of observation because in the packaging process on this machine there are still many defective products produced. The method used in this observation is Six Sigma with the DMAIC approach which consists of the Define, Measure, Analyze, Improve, Control stages. The results of data processing show that the sigma level value is 4.10, which means that the quality control process carried out by the company has been running well. However, more intense control still needs to be needed to minimize the possibility of defects. The causative factors that cause leakage defects in the primary packaging of xyz powder include four factors, namely Human, Machine, Method and Material factors. Then from the four factors, suggestions for improvement are given.